Implementing and Assessing a Standardized Protocol for Weaning Children Successfully From Extracorporeal Life Support. Issue 4 (8th February 2018) - Kubicki, Rouven; Höhn, René; Grohmann, Jochen; Fleck, Thilo; Reineker, Katja; Kroll, Johannes; Siepe, Matthias; Benk, Christoph; Klemm, Rolf; Humburger, Frank; Stiller, Brigitte
Abstract: Extracorporeal life support (ECLS) weaning is a complex interdisciplinary process with no clear guidelines. To assess ventricular and pulmonary function as well as hemodynamics including end‐organ recovery during ECLS weaning, we developed a standardized weaning protocol. We reviewed our experience 2 years later to assess its feasibility and efficacy. In 2015 we established an inter‐professional, standardized, stepwise protocol for weaning from ECLS. If the patient did not require further surgery, weaning was conducted bedside in the intensive care unit (ICU). Most of the weaning procedures are guided via echocardiography. Data acquisition began at baseline level, followed by four‐step course (each step lasting 10 min), entailing flow‐reduction and ending 30 min after decannulation. Moreover, data from the preprotocol era are presented. Between May 2015 and 2017, 26 consecutive patients (18 male), median age 177 days (2 days–20 years) required ECLS with median support of 4 (2–11) days. Excluding eight not weanable patients, 21 standardized weaning procedures were protocolled in the remaining 18 children. Our generally successful protocol‐guided weaning rate (with at least 24‐h survival) was 89%, with a discharge home rate of 58%. Practical application of the novel standard protocol seems to facilitate ECLS weaning and to improve its success rate. The protocol can be administered as part of standard bedside ICU assessment.